Elimination of Left-Right Reciprocal Coupling in the Adult Lamprey Spinal Cord Abolishes the Generation of Locomotor Activity - Messina, J. A.; St. Paul, Alison; Hargis, Sarah; Thompson, Wengora E.; McClellan, Andrew D. (Frontiers in Neural Circuits, 2017)
The contribution of left-right reciprocal coupling between spinal locomotor networks to the generation of locomotor activity was tested in adult lampreys. Muscle recordings were made from normal animals as well as from experimental animals with rostral midline (ML) spinal lesions (~13%35% body length, BL), before and after spinal transections (T) at 35% BL. Importantly, in the present study actual locomotor movements and muscle burst activity, as well as other motor activity, were initiated in whole animals by descending brain-spinal pathways in response to sensory stimulation of the anterior head. For experimental animals with ML spinal lesions, sensory stimulation could elicit well-coordinated locomotor muscle burst activity, but with some significant differences in the parameters of locomotor activity compared to those for normal animals. Computer models representing normal animals or experimental animals with ML spinal lesions could mimic many of the differences in locomotor activity. For experimental animals with ML and T spinal lesions, right and left rostral hemi-spinal cords, disconnected from intact caudal cord, usually produced tonic or unpatterned muscle activity. Hemi-spinal cords sometimes generated spontaneous or sensory-evoked relatively high frequency “burstlet” activity that probably is analogous to the previously described in vitro “fast rhythm”, which is thought to represent lamprey locomotor activity. However, “burstlet” activity in the present study had parameters and features that were very different than those for lamprey locomotor activity: average frequencies were ~25 Hz, but individual frequencies could be >50 Hz; burst proportions often varied with cycled time; “burstlet” activity usually was not accompanied by a rostrocaudal phase lag; and following ML spinal lesions alone, “burstlet” activity could occur in the presence or absence of swimming burst activity, suggesting the two were generated by different mechanisms. In summary, for adult lampreys, left and right hemi-spinal cords did not generate rhythmic locomotor activity in response to descending inputs from the brain, suggesting that left-right reciprocal coupling of spinal locomotor networks contributes to both phase control and rhythmogenesis. In addition, the present study indicates that extreme caution should be exercised when testing the operation of spinal locomotor networks using artificial activation of isolated or reduced nervous system preparations.